Diversity of endophytic fungal and bacterial communities in Ilex paraguariensis grown under field conditions - Pérez, María Laura (2016)
Fil: Pérez, María Laura. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.